Kesadaran Orang Tua terhadap Aplikasi Berbasis Ponsel Pintar untuk Anak-Anak Tunanetra dan Tuli di Yogyakarta, Indonesia: Penelitian - Pratiwi, Karina Satyani; Arjana, Adika Zhulhi; Ratnaningrum, Ayu Yunita; Sabana, Manusama Hasan; Chamidah, Atien Nur (Cermin Dunia Kedokteran, 2026)
Introduction: Smartphone-based applications (SBA) are currently available to help children with visual impairment (VI) and blindness progress to the next level of learning. This study aims to explore parental awareness of SBA to support the learning process of their visually impaired children. Methods: A cross-sectional study involving 27 children with VI and blindness. Parents were sent a questionnaire to be completed. The 20-item questionnaire measured the history of their children’s general and eye health, and SBA awareness and use, if any. Children were examined for general health and current eye conditions. Results: Blindness was 92.9%. The most common cause of blindness was retinopathy of prematurity. The majority went to a special school for the blind. Parents’ education level was mostly high school graduates. Only 22.2% parents were aware of the existence of SBA for children with VI and blindness. Conclusion: Parental awareness regarding smartphone-based applications (SBA) for children with VI and blindness was low.